ДВОКОНТУРНА СИСТЕМА РЕГУЛЮВАННЯ АСИНХРОННОГО ЕЛЕКТРОПРИВОДУ ОДНОЦИЛІНДРОВОГО ПОРШНЕВОГО КОМПРЕСОРА - Шуруб, Ю.В.; Попович, О.М.; Бібік, О.B. (Інститут електродинаміки НАН України, Київ, 2025)
A double-loop system of adjustable electric drives for single-cylinder piston compressors has been developed with a static proportional-differentiating regulator in the external speed control loop and an astatic proportional-integrating regulator in the internal torque control loop, taking into account the nonlinear dependence between the engine load moment and the angular displacement of its rotor. The method of tuning to the technical optimum was used to synthesize the internal torque loop regulator of an asynchronous motor at a fixed supply frequency. The example of mathematical modeling of the operating modes of an adjustable electric drive for a single-cylinder piston compressor based on the 4A63В2У3 induction motor shows that the use of a double-loop system allows for increasing the energy efficiency of the drive, improving THD and power factor, and reducing the amplitude of electromagnetic torque fluctuations compared to both unregulated and regulated drives using a single-loop system. References 23, figures 4, table 1.